Asymmetric causality between economic uncertainty and financial development: empirical evidence - Murdipi, Rafiqa (RSIS International, 2025)
This study analyses the asymmetric causal relationship between economic uncertainty and financial development across 86 countries. The employing of asymmetric Granger causality, as proposed by Hatemi-J (2012), indicates the presence of an asymmetric causal relationship between economic uncertainty and financial development. Positive change, namely a rise in economic uncertainty, adversely affects the growth of financial institutions. The advancement of financial institutions mitigates economic instability. Simultaneously, an escalation in economic uncertainty leads to heightened fluctuations in the financial market. Heightened fluctuations in the financial market will aggravate economic instability. This research will benefit policymakers, financial institutions, and investors by examining the dynamic link between economic uncertainty and financial development for risk reduction and forecasting.